A Tale of Two Radiation Belts: The Energy‐Dependence of Self‐Limiting Electron Space Radiation. Issue 20 (21st October 2021) - Olifer, L.; Mann, I. R.; Kale, A.; Mauk, B. H.; Claudepierre, S. G.; Baker, D. N.; Spence, H. E.; Ozeke, L. G.
Abstract: The flux of energetic electrons in the terrestrial Van Allen Belts varies by orders of magnitude during a magnetic storm. Here, we show how the dynamics of these electrons are clearly separated by energy into two distinct populations which are governed by different storm time behavior. We reveal how self‐limiting processes, described theoretically by Kennel and Petschek (1966), https://doi.org/10.1029/JZ071i001p00001, govern the energy‐dependent dynamics of the electrons. For terrestrial magnetic storms, accelerated electrons with energies below ∼ 850 keV quickly reach a maximum energy‐dependent differential flux level which is almost the same in every storm. Higher energy electrons typically do not reach a limiting flux and instead are governed by the differential impacts of competing acceleration and loss mechanisms. In general, electron fluxes saturate at the Kennel‐Petschek limit first at lower energies, impacting higher energies later in the storm. For the most intense storms, the maximum energy at which the fluxes are capped can also increase. Plain Language Summary: Very high energy electrons in near‐Earth space constitute a space radiation threat to spacecraft. All of this space radiation is traveling close to the speed of light. However, as we show here, nature remarkably imposes a limit to the number of these space radiation particles which can be generated once the acceleration is strong enough. At lower energies, where the numbers of particles are typically larger, we show that there is an absolute limit to the severity of the space radiation. That is, there is a natural limit to how bad this radiation can get. At higher energies, however, while there is still a theoretical limit it is almost never reached. Our results are based on the interpretation of a 50‐year‐old theory developed by Kennel and Petschek (1966), https://doi.org/10.1029/JZ071i001p00001 but which has been largely untested until now. None of the modern radiation belt models incorporate these effects, and our results provide an important input for both improved radiation specification and for assessing worst case space radiation threats. As we show here, depending on energy, it can be the best of times, and the worst of times, for the extremes of the level of space radiation reached during a space storm. Key Points: Superposed epoch analysis of 70 geomagnetic storms reveals drastically different behavior of radiation belt electrons depending on energy Electrons with energies below ∼850 keV are revealed to be strongly affected by self‐limiting Kennel‐Petschek processes in almost every storm Generally, the flux of higher energy particles is not capped and only becomes self‐limited for the most intense and long‐lasting storms